2009
DOI: 10.1186/1743-422x-6-47
|View full text |Cite
|
Sign up to set email alerts
|

Detection and phylogenetic analysis of Orf virus from sheep in Brazil: a case report

Abstract: Background: Orf virus (ORFV), the prototype of the genus Parapoxvirus (PPV), is the etiological agent of contagious ecthyma, a severe exanthematic dermatitis that afflicts domestic and wild small ruminants. Although South American ORFV outbreaks have occurred and diagnosed there are no South American PPV major membrane glycoprotein B2L gene nucleotide sequences available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 14 publications
2
40
0
1
Order By: Relevance
“…ORFVs from the same outbreak have been reported [1,5,6,12,14,24]. Guo et al reported an outbreak of ORFV infection in a zoo, in which a single ORFV likely infected musk ox (Ovibos moschatus), domestic Shetland sheep (Ovis aries) and Sichuan takin (Budorcas taxicolor tibetana), but the amino acid sequence of the viral envelope gene contained one or two substitutions in each animal [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORFVs from the same outbreak have been reported [1,5,6,12,14,24]. Guo et al reported an outbreak of ORFV infection in a zoo, in which a single ORFV likely infected musk ox (Ovibos moschatus), domestic Shetland sheep (Ovis aries) and Sichuan takin (Budorcas taxicolor tibetana), but the amino acid sequence of the viral envelope gene contained one or two substitutions in each animal [12].…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analyses of the viral envelope gene indicate that contagious pustular dermatitis in Japanese serows is mainly caused by ORFV [18,19]. However, only a partial sequence of the envelope gene was analyzed in these studies, and in other countries, sequence variations occur in the envelope gene of ORFVs isolated from the same outbreaks [1,5,6,12,14,24]. In general, the amino acid sequences of the genes encoding viral structural proteins, such as the envelope, are relatively well conserved, but the detailed genetic relationship between the PPVs of the recent and earlier outbreaks in Japanese serows is unclear.…”
mentioning
confidence: 99%
“…PCR was evaluated as a fast, cheap and valid technique for virus detection. The most common genes used are B2L gene; a highly immunogenic envelope gene [19,26,28] and Orf F1L gene; an immunodominant gene [1,9,12,14,15,18,19,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of new ORFV strains in Brazil seems to occur through the import of animals in order to improve herd genetics (Abrahão et al, 2009). …”
Section: Figure 10: Ultrathin Section Of the Crusts Fragments Observmentioning
confidence: 99%